Analysis of Maq?sid Asy-Syari'ah Regarding Marriage Limits in Law Number 16 of 2019 Concerning Marriage - Kamila Hayati Alkhifny (Journal of Law and Social Politics, 2023)
The divorce rate in indonesia continues to increase. One 0f the reasons is the lack of readiness of the husband and/or wife for marriage. Marriages that are carried out at a very early age result in a lack of readiness of the bride and groom to get married. The stipulation of the marriage age limit which was originally 19 years for men and 16 years for women was changed to 19 years for men and women in law number 16 of 2019. However, early marriages are still common in indonesia, so the divorce rate is still quite high. Then the question arises that whether the regulation of changing the age limit for marriage can change the value of marriage in indonesia for the better or is it just a meaningless regulation. But of course, a regulation is made to improve the existing situation and benefit the community. This study aims to find out what the purpose of law no. 16 of 2019 is by examining it with the value of maq?sid ash-syar?'ah. This study uses qualitative research methods, and the data collected comes from a literature review which was analyzed by descriptive analysis method. The results of this study are that the renewal of the marriage age limit in law number 16 of 2019 is in line with the values in maq?sid ash-syar?'ah namely hif? ad-d?n, hif? an-nafs, hif? al-aql, hif? an-nasal, and hif? al-m?l. Marriage at a more mature age will improve the quality of religion in the family, protect the physical and psychological health of family members, strengthen the family foundation in dealing with household problems, form quality offspring, and maintain family finances